Studies in Syriac Spirituality: revised, enlargedand updated edition - Thonippara, Francis (Asian Horizons, 2008)
Sebastian Brock, Studies in Syriac Spirituality, revised, enlarged and updated edition, Bangalore: Dharmaram Publications, 2008, pages XII + 273, ISBN 81-89958-17-8.